2005
DOI: 10.1002/biof.5520240103
|View full text |Cite
|
Sign up to set email alerts
|

Studies of phospholipid oxidation by electrospray mass spectrometry: From analysis in cells to biological effects

Abstract: The oxidation of lipids is important in many pathological conditions and lipid peroxidation products such as 4-hydroxynonenal (HNE) and other aldehydes are commonly measured as biomarkers of oxidative stress. However, it is often useful to complement this with analysis of the original oxidized phospholipid. Electrospray mass spectrometry (ESMS) provides an informative method for detecting oxidative alterations to phospholipids, and has been used to investigate oxidative damage to cells, and low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 78 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…They are a convenient method to identify oxidized phospholipids, most of which are readily ionizable. An important advantage compared with GC-MS is that analytes can be detected directly, without the chemical manipulation necessary to release the fatty acid chains and derivatize them to generate the volatile species required for GC (116). Thus, these soft ionization methods tend to be simpler, less open to handling artifacts, and information on the intact phospholipid structure is not lost.…”
Section: Ms In Modern Oxidative Lipidomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are a convenient method to identify oxidized phospholipids, most of which are readily ionizable. An important advantage compared with GC-MS is that analytes can be detected directly, without the chemical manipulation necessary to release the fatty acid chains and derivatize them to generate the volatile species required for GC (116). Thus, these soft ionization methods tend to be simpler, less open to handling artifacts, and information on the intact phospholipid structure is not lost.…”
Section: Ms In Modern Oxidative Lipidomicsmentioning
confidence: 99%
“…However, adjustment of the solvent systems with ionization modifiers can enable detection in the opposite ionization mode if required: for example, although PC has a constitutive positive charge on the choline moiety, phosphocholine-containing lipids can be observed in negative ion mode as formate or acetate adducts (20). As PC is both very abundant and easily observable in either mode, much research had previously focused on identifying oxidation products of unsaturated PCs (20,116), although to address this knowledge gap increasing studies on oxidation of phopholipids with other headgroups are being undertaken, including PE, PS, and CL (26,70,74,132). The principles of fatty acyl group oxidation are common to all the phospholipids, and it is well established that hydroperoxides, hydroxides, epoxides, and chlorinated species can be detected, according to the mass increments and fragmentation patterns.…”
Section: Fig 4 Lipidomics Approachesmentioning
confidence: 99%
“…These modifications can be induced, in vivo, by enzymatic or non-enzymatic reactions (induced by radicals generated by radiation or metal catalyzed systems) (Fruhwirth, et al, 2007). Detailed identification of the oxidation products generated under oxidative conditions of PCs have been performed using mass spectrometry (MS) (Marathe et al, 2000;Reis et al, 2004aReis et al, ,b, 2007Spickett and Dever, 2005), but little attention has been dedicated to the oxidative modifications in PEs (Morand et al, 1988;Ramanadham et al, 1993;Engelmann et al, 1994;Bacot et al, 2003Bacot et al, , 2007Maeba and Ueta, 2003;Tsuji et al, 2003;Bernoud-Hubac et al, 2004). From those, most of the investigation was focused on the study of the adducts resulting from the interaction of PEs and aldehydes, generated from lipid oxidation (Bacot et al, 2003(Bacot et al, , 2007Tsuji et al, 2003;Bernoud-Hubac et al, 2004), while others report on the potential antioxidant properties of plasmenyl ethanolamines (Morand et al, 1988;Ramanadham et al, 1993;Engelmann et al, 1994;Maeba and Ueta, 2003), and only one paper reports the identification of PE oxidation products by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Gugiu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many reported studies [75,[77][78][79][80][81][82][83] have shown that oxidized PL cause harmful effects to human health as they play physiopathological roles in developing diseases such as age-related and chronic diseases, acute lung injury, atherosclerosis, inflammation and decrease immune response. PL oxidation products such as hydroperoxyl, hydroxyl, aldehyde and epoxy groups that are potentially important in the progression of atherosclerosis and inflammation [80]. For instance, by activating the receptor for the platelet-activating factor (PAF), oxidized PL induce platelet aggregation [84][85][86].…”
Section: Dangers Of Auto-oxidation Of Mplmentioning
confidence: 99%